Application of Fe3O4@Silica Sulfuric Acid as a Magnetic Nanocatalyst for the Synthesis of Rhodamine Derivatives. Issue 21 (1st June 2018) - Vajekar, Shailesh N.; Shankarling, Ganapati S.
Abstract: A green protocol for the synthesis of novel rhodamine derivatives employing a highly efficient and recyclable magnetic Fe3 O4 @silica sulfuric acid nanocatalyst in greener solvent ethylene glycol is demonstrated. In comparison with the known methods for the synthesis of rhodamines, our method offers several benefits such as mild reaction conditions, short reaction time (5 h) and high yield (up to 79%) of the products. Interestingly, the magnetically separable nanocatalyst was reused at least five times without significant loss in catalytic activity. All the novel derivatives are well characterized by 1 H NMR, 13 C NMR, and mass spectrometry. Abstract : A green approach for the synthesis of novel rhodamine derivatives is demonstrated by reacting 3‐(N, N‐disubstituted amino)phenol and 2, 3‐diphenyl maleic anhydride by using a highly efficient and recyclable magnetic Fe3 O4 @silica sulfuric acid nanocatalyst in greener solvent ethylene glycol.